Coordination behaviour of new open chain and macrocyclic peptidomimetic compounds with copper(ii)1. Issue 89 (27th September 2015) - Wadhavane, Prashant D.; Gorla, Lingaraju; Ferrer, Armando; Altava, Belén; Burguete, M. Isabel; Izquierdo, M. Ángeles; Luis, Santiago V.
<x xml:space="preserve">Abstract</x> Two valine-derived bis(amino amides) ligands have been prepared and fully characterized.